Health risk assessment of hazardous VOCs and its associations with exposure duration and protection measures for coking industry workers. (15th December 2022) - Cheng, Long; Wei, Wei; Guo, Aimin; Zhang, Chengzhou; Sha, Kechang; Wang, Ruipeng; Wang, Kai; Cheng, Shuiyuan
Abstract: Coke making is extremely problematic from the environment and health perspectives, as the massive hazardous volatile organic compounds (HVOCs) being driven off during the coking process. Here, we conducted a health risk assessment study on coking workers, through on-situ HVOCs measurements and questionnaire investigation on activity time parameters and protection measures. The ambient HVOCs at major working stations were 58.4–376.5 μg/m 3 with relative deviation of 59.4% for the certain station. The total working hours during career would reach 43283–51695 h, and protection efficiency (PE) to resist HVOCs inhalation ranged from 16% to 87%. According to the exposure evaluation model recommended by the U.S. EPA, there was little non-cancer risk for the workers at most positions with hazard quotient (HQ) value of less than 1; however, the cancer risk widely existed with lifetime cancer risk (LCR) value of 3.6–15.0 × 10 −6, in which benzene, 1, 2-dichloropropane, 1, 2-dichloroethane, and 1, 3-butadiene were dominant inducers. The cancer risk regarding the large plants was about 28.6% lower compared to the small and medium plants, due to the greater PE. In terms of the response of the health risk to exposure duration (ED, working years) and PE, non-cancer risk effectively responded only for the byproduct recovery stations, while cancer risk more sensitively responded for all stations. Health risk management therefore is essential, and the potential health hazards can be avoided by limiting ED and strengthening PE. For workers in coking, byproduct recovery and office areas, the PE should be higher than 93.8%, 97.7% and 77.3% under the ED of 20 years, the ED in three areas should be lower than 12.5 years, 4.5 years and 30 years under PE of 90%, respectively. Graphical abstract: Image 1 Highlights: HVOCs species regarding 11 work stations of coking plant were measured. The activity time and protection measure of coking workers were investigated. Most positions have less non-cancer risk but cancer risk. The cancer risk value of various positions ranged from 3.6 × 10 −6 –1.5 × 10 −5 . The security recommendations are given based on health risk response study.